Inter-Establishment Complex Musculoskeletal Care Pathways in Montreal: Timeline of a Collaboration Involving a Research Team Within a Continuous Quality Improvement Initiative - Marie Beauséjour; Martin Sasseville; Aurélie Vigné; Sophie Riendeau; Stephanie Gould; Kelly Thorstad (SAGE Publishing, 2024)
Children and adolescents with complex musculoskeletal conditions may receive health care that requires at least 1 transfer between 4 specialized pediatric establishments in the Montreal region (Québec, Canada). This may result in challenges in navigating the system. A collaborative approach, aiming to make the inter-establishment care pathways seamless and to improve the integration of musculoskeletal health services, brought together key stakeholders including a research team. The aim of this paper is to describe the timeline of the collaborative approach's key milestones and activities and, more specifically, to describe the context, process, and outputs of the involvement of researchers in support of a continuous quality improvement project based on an integrated approach. The descriptive timeline was constructed from a qualitative document analysis of the project-related gray literature (n = 80 documents) and was validated and interpreted with key stakeholders. The results showed how the collaborative project was set up and operated, as well as what solutions were developed and implemented. The strategies on how the research team was involved in the integrated approach in addition to its research activities were also described. Conclusions suggest practice recommendations for creating change processes by integrating research, service evaluation and clinical audit into quality improvement projects.